The role of HDAC2 inhibition in cardioprotection against doxorubicin-induced myocardial injury - Liu, Jinsha; Fu, Wenwen; Wang, Xue; Liang, Zuowen; Meng, Fanbo (Frontiers in Cardiovascular Medicine, 2025)
IntroductionThe molecular mechanisms underlying cardioprotection against doxorubicin (DOX)-induced myocardial injury are poorly understood. Histone deacetylase 2 (HDAC2) plays a significant role in oxidative stress, apoptosis, and mitochondrial dysfunction and is implicated in many human diseases, This study investigated the relationship between HDAC2 expression and DOX-induced myocardial injury using the in vivo rat model of DOX-induced cardiotoxicity and in vitro experiments with the H9c2 cardiomyocytes.MethodsThe rat model of DOX-induced myocardial injury was established by administering DOX via intraperitoneal injections. HDAC2 expression was suppressed by administering rats with sodium butyrate (SB) via intraperitoneal injections. Echocardiography measurements were performed at baseline and on day 15 post-treatment. The rats were euthanized on day 15 and cardiac tissues were harvested. The cardiac tissue samples were analyzed by hematoxylin and eosin H&E staining, immunohistochemistry, Masson staining, Sirius Red staining, TUNEL staining, and western blotting to determine the status of HDAC2 expression and myocardial apoptosis. In the vitro experiments, H9c2 cells were treated with DOX. HDAC2 expression was suppressed using sodium butyrate or transfected cells with the shRNA knockdown HDAC2 (shHDAC2). The H9c2 cells from different groups were analyzed by Rt-qPCR, CCK-8 cell viability assay, and western blotting to determine the status of HDAC2 expression and cardiomyocyte apoptosis.ResultsDOX treatment induced cardiac dysfunction in rats. The cardiac tissues of the DOX-treated rats and H9c2 cells showed significantly higher levels of HDAC2 compared to the corresponding controls. However, inhibition of HDAC2 significantly mitigated DOX-induced myocardial injury in rats. This suggested a strong association between HDAC2 expression and DOX-induced myocardial injury. In the H9c2 cells, HDAC2 knockdown by shHDAC2 alleviated DOX-induced apoptosis by enhacing AKT phosphorylation. These findings demonstrated that HDAC2 silencing protected against DOX-induced cardiomyocyte apoptosis by activating the PI3K/AKT signaling pathway.ConclusionSuppressing HDAC2 protected against DOX-induced cardiomyocyte apoptosis by activating the PI3K/AKT signaling pathway. Therefore, HDAC2 is a promising therapeutic target for mitigating DOX-induced myocardial injury.